CLTC‐ALK fusion as a primary event in congenital blastic plasmacytoid dendritic cell neoplasm. Issue 1 (21st October 2013) - Tokuda, Kiriko; Eguchi‐Ishimae, Minenori; Yagi, Chihiro; Kawabe, Mika; Moritani, Kyoko; Niiya, Toshiyuki; Tauchi, Hisamichi; Ishii, Eiichi; Eguchi, Mariko
<x xml:space="preserve">Abstract</x> Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a subtype of acute myeloid leukemia, affecting mainly the elderly. It is thought to be derived from plasmacytoid dendritic cell precursors, which frequently present as cutaneous lesions. We have made a detailed analysis of an infant with BPDCN, who manifested with hemophagocytic lymphohistiocytosis. The peripheral blood leukocytes revealed the t(2;17;8)(p23;q23;p23) translocation and a CLTC‐ALK fusion gene, which have never been reported in BPDCN or in any myeloid malignancies thus far. Neonatal blood spots on the patient's Guthrie card were analyzed for the presence of the CLTC‐ALK fusion gene, identifying the in utero origin of the leukemic cell. Although the leukemic cells were positive for CD4, CD56, CD123, and CD303, indicating a plasmacytoid dendritic cell phenotype, detailed analysis of the lineage distribution of CLTC‐ALK revealed that part of monocytes, neutrophils, and T cells possessed the fusion gene and were involved in the leukemic clone. These results indicated that leukemic cells with CLTC‐ALK originated in a multipotent hematopoietic progenitor in utero. This is the first report of the CLTC‐ALK fusion gene being associated with a myeloid malignancy, which may give us an important clue to the origin of this rare neoplasm. © 2013 Wiley Periodicals, Inc.